Proteomic analyses of serous and endometrioid epithelial ovarian cancers – Cases studies – Molecular insights of a possible histological etiology of serous ovarian cancer. Issue 5 (18th June 2013) - Longuespée, Rémi; Gagnon, Hugo; Boyon, Charlotte; Strupat, Kurstin; Dauly, Claire; Kerdraon, Olivier; Ighodaro, Adesuwa; Desmons, Annie; Dupuis, Jocelyn; Wisztorski, Maxence; Vinatier, Denis; Fournier, Isabelle; et al.
<x xml:space="preserve">Abstract</x> Purpose Epithelial ovarian carcinogenesis may occur de novo on the surface of ovarian mesothelial epithelial cells or from cells originating in other organs. Foreign Müllerian cell intrusion into the ovarian environment has been hypothesized to explain the latter scenario. In this study, MALDI MS profiling technology was used to provide molecular insights regarding these potentially different mechanisms. Experimental design Using MALDI MS profiling, the molecular disease signatures were established in their anatomical context. MALDI MS profiling was used on serous and endometrioid cancer biopsies to investigate cases of epithelial ovarian cancer. We then applied bioinformatic methods and identification strategies on the LC‐MS/MS analyses of extracts from digested formalin‐fixed, paraffin‐embedded tissues. Extracts from selected regions (i.e. serous ovarian adenocarcinoma, fallopian tube serous adenocarcinoma, endometrioid ovarian cancer, benign endometrium, and benign ovarian tissues) were performed, and peptide digests were subjected to LC‐MS/MS analysis. Results Comparison of the proteins identified from benign endometrium or three ovarian cancer types (i.e. serous ovarian adenocarcinoma, endometrioid ovarian adenocarcinoma, and serous fallopian tube adenocarcinoma) provided new evidence of a possible correlation between the fallopian tubes and serous ovarian adenocarcinoma. Here, we propose a workflow consisting of the comparison of multiple tissues in their anatomical context in an individual patient. Conclusion and clinical relevance The present study provides new insights into the molecular similarities between these two tissues and an assessment of highly specific markers for an individualized patient diagnosis and care.